Migration of Pleistocene shorelines across the Palaeo-Agulhas Plain: Evidence from dated sub-bottom profiles and archaeological shellfish assemblages. (1st May 2020) - Cawthra, Hayley C.; Anderson, Robert J.; De Vynck, Jan C.; Jacobs, Zenobia; Jerardino, Antonieta; Kyriacou, Katharine; Marean, Curtis W.
Abstract: Intertidal zones on shorelines are geologically complex features of the coastal plain, shaped by heterogeneous substrate lithologies. Palaeocoastlines have been heavily modified by sea-level change, ocean currents, wind, waves and swell. Rocks and sediments along intertidal zones create rich habitats for biogenic forms including shellfish, which are highly sensitive to subtle variations in underlying lithology. Here, we assess Pleistocene shoreline migrations on the south coast of South Africa in relation to fluctuating sea-levels and changes in sediment supply. The study area extends from Still Bay to Mossel Bay, South Africa, with a particular focus on Pinnacle Point. Our goal is to better understand the changes to the intertidal zone along these palaeocoastlines and how this may have affected marine resources available to early humans. We interpret marine geological records at select time slices along sub-bottom profiled transects that run perpendicular to the coast. We describe the character of specific shorelines to establish expectations of coastline character which we then compare to archaeological records at Pinnacle Point. We base our interpretations on (1) significant events in Pleistocene glacio-eustatic and depositional records, such as widespread deposition of coastal sand dunes at ∼90, ∼74 and ∼50 ka [MIS 5e–MIS 4], and (2) empirical evidence from high-resolution records of shellfish assemblages at the archaeological sites of PP13B and PP5-6. We demonstrate a prevalence of dissipative beaches and mixed coasts on Pleistocene sea-level lowstands on the coast of the Palaeo-Agulhas Plain. This differs significantly from the modern coastline with its significance of rocky shorelines. Highlights: Changes to intertidal zones along Pleistocene palaeocoastlines and the effect on marine resources available to early humans. Prevalence of dissipative beaches and mixed coasts on Pleistocene sea-level lowstands on the coast of the Palaeo-Agulhas Plain. Contrasting palaeoshorelines to the modern Cape South Coast. Alternating episodes of dune building and palaeosol development, expressed as planation surfaces in the seismic record. Increased occurrence of dissipative beaches when sea level reaches a lowstand point of 47 m bMSL, and below. Reflective beaches below this depth on the Palaeo-Agulhas Plain may have been associated with mixed rocky/sandy shorelines.